BANKING TRANSACTIONS USING FINANCIAL TECHNOLOGY EXPANDED DURING THE COVID 19 PANDEMIC - Hardi Fardiansyah; PA. Andiena Nindya Putri; Ariawan Ariawan (SEAN Institute, 2023)
This study was conducted to determine the growth of Fintech transactions in banking during the Covid-19 pandemic. As we all feel that the covid-19 pandemic outbreak is a serious threat to life and the economy. This has an impact on all business sectors which has a bad influence on world financial inclusion, especially in Indonesia. This impact is also felt by the banking sector. As a financial intermediary institution that prioritizes services to the community (customers), banks are increasingly aggressively carrying out their business activities on a technological basis. Financial technology is a base that continues to be rushed in its development and updating to support cash less transactions that allow transactions without cash and without face to face. The opening of payment channels through leading and well-known start-ups continues to be established so that it is possible to interlock in transactions. Peer to peer (P2P) is one of the right ways to help strengthen inclusiveness for businesses and customers. Creating convenience in every transaction is an obligation for every banking institution. Facilitating the reach of services to each individual is also an expectation that must be achieved and realized. Financial technology (Fintech) is the right tool to build an image in the eyes of the community as a partner / user.